ANALISIS DAN RANCANGAN SISTEM INFORMASI LAYANAN POSYANDU BERBASIS WEB PADA POSYANDU ALPOKAT - Bhakti Sihanjono; Seneng Rahayu; Navita Apriani; Ilham Albana (CV. Denasya Smart Publisher, 2026)
Posyandu is a community-based health service that plays an important role in monitoring maternal and child health. However, the data management process at Posyandu Alpokat is still carried out manually using record books, causing several problems such as difficulties in data retrieval, risk of data loss, and slow report generation. This study aims to design a Web-Based Posyandu Information System that is designed to assist in managing toddler data, pregnant women data, health examination records, child growth monitoring, and digital report generation. The methods used in this study include requirements analysis, system design using Data Flow Diagrams (DFD), Entity Relationship Diagrams (ERD), and database design. The results of this study indicate that the designed system can improve the effectiveness and efficiency of Posyandu data management, facilitate information retrieval, increase data recording accuracy, and support more organized and modern public health services.